Novel Insights into the Molecular Features and Regulatory Mechanisms of Mitochondrial Dynamic Disorder in the Pathogenesis of Cardiovascular Disease. (20th February 2021) - Tan, Ying; Xia, Fengfan; Li, Lulan; Peng, Xiaojie; Liu, Wenqian; Zhang, Yaoyuan; Fang, Haihong; Zeng, Zhenhua; Chen, Zhongqing
Abstract : Mitochondria maintain mitochondrial homeostasis through continuous fusion and fission, that is, mitochondrial dynamics, which is precisely mediated by mitochondrial fission and fusion proteins, including dynamin-related protein 1 (Drp1), mitofusin 1 and 2 (Mfn1/2), and optic atrophy 1 (OPA1). When the mitochondrial fission and fusion of cardiomyocytes are out of balance, they will cause their own morphology and function disorders, which damage the structure and function of the heart, are involved in the occurrence and progression of cardiovascular disease such as ischemia-reperfusion injury (IRI), septic cardiomyopathy, and diabetic cardiomyopathy. In this paper, we focus on the latest findings regarding the molecular features and regulatory mechanisms of mitochondrial dynamic disorder in cardiovascular pathologies. Finally, we will address how these findings can be applied to improve the treatment of cardiovascular disease.